Surface states influence in Al Schottky barrier of Ge nanowires - Kamimura, Hanay; Simon, Ricardo A.; Berengue, Olivia M. [UNESP]; Amorim, Cleber A.; Chiquito, Adenilson J.; Leite, Edson R. (Springer Nature, 2013)
Aiming the understanding of how the application to devices is affected by the presence of oxygen in semiconductor nanostructures, Al/Ge-nanowires Schottky devices were fabricated without any previous treatment to remove the native oxide from nanowires' surface, originated during the growth process. Electronic transport properties of these devices were investigated and it was observed that interface states originated from the disordered oxide layer effectively pinned the Fermi level at the Ge surface, affecting Schottky barriers. Numerical calculations were made to complement this study agreeing with experiments. © 2013 Materials Research Society.